2003
DOI: 10.1080/16226510390856439
|View full text |Cite
|
Sign up to set email alerts
|

Phytoremediation of Pyrene in a Cecil Soil under Field Conditions

Abstract: We evaluated the effects of annual ryegrass (Lolium multiflorum Lam.) and phosphorus (P) availability on the dissipation of pyrene added at a concentration of approximately 600 mg kg-1 dry soil in the top 7.5 cm of a Cecil loamy sand (fine, kaolinitic, thermic Typic Kanhapludults) in a 10-month experiment under field conditions in Clemson, South Carolina. Plastic canopies were installed to prevent flooding of plots and raindrop dispersion of pyrene. Treatment factors were pyrene, vegetation, and available P le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…The lack of a pyrene degradation response to the presence of plants may be due to the fact that root exudates and other organic compounds provided accessible and readily bioavailable C to microorganisms, thus reducing degradation of the more complex pyrene C source. The lack of a response of pyrene degradation to the presence of plants has been reported previously (Lalande et al 2003;Olexa et al 2000). In the absence of plants, increased soil N concentrations had a negative effect on pyrene biodegradation.…”
Section: Pyrene Degradationmentioning
confidence: 84%
See 2 more Smart Citations
“…The lack of a pyrene degradation response to the presence of plants may be due to the fact that root exudates and other organic compounds provided accessible and readily bioavailable C to microorganisms, thus reducing degradation of the more complex pyrene C source. The lack of a response of pyrene degradation to the presence of plants has been reported previously (Lalande et al 2003;Olexa et al 2000). In the absence of plants, increased soil N concentrations had a negative effect on pyrene biodegradation.…”
Section: Pyrene Degradationmentioning
confidence: 84%
“…Reilley et al (1996) and Chen and Banks (2004) measured pyrene in vegetated soils and found that plants and their associated microorganisms enhanced pyrene degradation. In contrast, Lalande et al (2003) reported that there was a significantly higher degradation rate in unvegetated treatments when evaluating the effect of ryegrass (Lolium multiflorum Lam.) on pyrene degradation.…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…Phytoremediation, the use of plants to degrade or remove contaminants, has been shown to be effective for petroleum (Reilley et al, 1996;Ferro et al, 1999;Liste et al, 1999;Lalande et al, 2003). Root exudates may provide a source of carbon and energy for microbes, stimulating metabolism and/or co-metabolism of contaminants.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have demonstrated that certain plant species could enhance the degradation of PHC in the rhizosphere (Euliss et al 2008;Peng et al 2009) by increasing the number and activity of soil microorganisms compared with bulk soil (Macek et al 2000;Kaimi et al 2006). Nevertheless, other plant species seemed not to be able to improve remediation efficiency (Lalande et al 2003;Euliss et al 2008). In weathered contaminated soils, phytoremediation face some additional challenges that are not present in recently contaminated soils, like lower chemical extractability and bioavailability of contaminants (Phillips et al 2009).…”
Section: Introductionmentioning
confidence: 96%